Fatigue-induced alterations of static and dynamic postural control in athletes with a history of ankle sprain - Steib, Simon; Zech, Astrid; Hentschke, Christian; Pfeifer, Klaus (Journal of athletic training, 2013)
Sensorimotor control is impaired after ankle injury and in fatigued conditions. However, little is known about fatigue-induced alterations of postural control in athletes who have experienced an ankle sprain in the past.To investigate the effect of fatiguing exercise on static and dynamic balance abilities in athletes who have successfully returned to preinjury levels of sport activity after an ankle sprain.Cohort study.University sport science research laboratory.30 active athletes, 14 with a previous severe ankle sprain (return to sport activity 6-36 months before study entry; no residual symptoms or subjective instability) and 16 uninjured controls.Fatiguing treadmill running in 2 experimental sessions to assess dependent measures.Center-of-pressure sway velocity in single-legged stance and time to stabilization (TTS) after a unilateral jump-landing task (session 1) and maximum reach distance in the Star Excursion Balance Test (SEBT) (session 2) were assessed before and immediately after a fatiguing treadmill exercise. A 2-factorial linear mixed model was specified for each of the main outcomes, and effect sizes (ESs) were calculated as Cohen d.In the unfatigued condition, between-groups differences existed only for the anterior-posterior TTS (P = .05, ES = 0.39). Group-by-fatigue interactions were found for mean SEBT (P = .03, ES = 0.43) and anterior-posterior TTS (P = .02, ES = 0.48). Prefatigue versus postfatigue SEBT and TTS differences were greater in previously injured athletes, whereas static sway velocity increased similarly in both groups.Fatiguing running significantly affected static and dynamic postural control in participants with a history of ankle sprain. Fatigue-induced alterations of dynamic postural control were greater in athletes with a previous ankle sprain. Thus, even after successful return to competition, ongoing deficits in sensorimotor control may contribute to the enhanced ankle reinjury risk.
Gesehen am 13.07.2022